The Role of Media Exposure on Coordination in the Humanitarian Setting. Issue 5 (18th January 2017) - Eftekhar, Mahyar; Li, Hongmin; Van Wassenhove, Luk N.; Webster, Scott
Abstract : Despite high demand and resource limitations, humanitarian organizations (HOs) typically do not share resources and/or coordinate in the field. While coordination enhances operational performance and saves costs, the general perception is that it dilutes the media attention that individual organizations might receive, and negatively influences their future donation income. In this study, we empirically unveil the impact of media exposure and operational performance on the donations obtained by HOs. Then, based on the empirical results, we develop a stylized model to characterize the structure of preferred coordination policies with respect to an organization's funding source and main mandate. Our findings shed light on the incentives and dynamics that drive behaviors in humanitarian operations and provide insights for policy makers on designing and implementing mechanisms that encourage humanitarian coordination.